2008
DOI: 10.1002/ajhb.20861
|View full text |Cite
|
Sign up to set email alerts
|

Physical growth in schoolchildren from Argentina: Comparison with Argentinean and CDC/NCHs growth references

Abstract: The aim of this study was to assess the physical growth of schoolchildren from Argentina by comparison with the CDC/NCHS and Argentinean growth references (AGR), to contribute to the discussion about the use of local or international references for the assessment of growth in developing countries. Weight and height were measured in 3,411 schoolchildren aged 5-14 years. Data were log-transformed and compared with both references by paired samples t-test (CI = 0.95; alpha = 0.005). The boys' weights were greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
1
6
0
6
Order By: Relevance
“…The potential problem associated with the secular trend of an erroneously decreased number of short children being identified has previously been flagged by Wit et al. 38 Similarly, that differences in mean heights between contemporary population samples and the CDC 2000 charts vary with age group has also been noted previously 16,20,22,39 . This study recognises an actual diagnostic problem associated with the use of CDC 2000 data in Australia and notes that it may vary with the age and at certain times also with the gender of the child being investigated.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The potential problem associated with the secular trend of an erroneously decreased number of short children being identified has previously been flagged by Wit et al. 38 Similarly, that differences in mean heights between contemporary population samples and the CDC 2000 charts vary with age group has also been noted previously 16,20,22,39 . This study recognises an actual diagnostic problem associated with the use of CDC 2000 data in Australia and notes that it may vary with the age and at certain times also with the gender of the child being investigated.…”
Section: Discussionsupporting
confidence: 53%
“…Height distributions have changed over time 6–8,10,14,16,17 and vary between populations when compared to CDC charts 16,18–22 . The height distributions we see in Australia today are different to those represented by the CDC curves 4,5,9,15 .…”
Section: Introductionmentioning
confidence: 87%
“…Heightfor-age z-scores and weight-for-age z-scores were calculated using Epi-Info software, which allows for comparisons with U.S. reference girls (Epi Info, 2005). The U.S. reference data were used as there is no standard regional reference population with which to make comparison, as compared to other international growth studies (Orden et al, 2009). Height was measured in centimeters using a portable field anthropometer (GPM, Seritex Inc.) with the subjects standing on level ground without shoes.…”
Section: Methodsmentioning
confidence: 99%
“…Another study on the same population (Orden et al, 2009(Orden et al, ), surveyed between 2005(Orden et al, -2007, evidenced that height of schoolchildren aged 5-14 years, showed a clear dissociation from the national reference and minor differences from CDC. Around puberty, however, the children's height fell short of CDC, especially the girls, whose values approached those of their Argentinian peers.…”
Section: Discussionmentioning
confidence: 94%